Mono and binuclear cobalt(II) mixed ligand complexes containing 1,10-phenanthroline and adenine using 1,3-diaminopropane as a spacer: synthesis, characterization, and antibacterial activity investigations - Atakilt Abebe; Yosef Bayeh; Minale Belay; Tesfay Gebretsadik; Madhu Thomas; Wolfgang Linert (SpringerOpen, 2020)
Abstract Background Coordination compounds, in particular cobalt(II) mixed ligand complexes containing 1,10-phenantroline, have drawn the attention of many investigators as some of them are showing antimicrobial activities. Result Herein, we report three novel mixed ligand complexes of cobalt(II) having the formulae [Co(L 1)2(H2O)2]Cl2, [Co(L 1)2(L 2)(H2O)]Cl2 and [Co2(L 1)4(L 2)2(L 3)]Cl4 (L 1 = 1,10-phenanthroline, L 2 = adenine, L 3 = 1,3-diaminepropane) were synthesized and characterized by elemental analysis, conductivity measurement, infrared, and UV-Vis spectroscopic techniques. Octahedral geometries are proposed to all the complexes. In vitro antibacterial activities of the ligands, salt, and metal complexes were tested on four pathogenic bacteria (Staphylococcus aureus, Salmonella typhus, Escherichia coli, and Staphylococcus epidermis) using disc diffusion method. Conclusions It is interesting to note that the newly synthesized cobalt(II) complexes are active against gram negative bacteria (Escherichia coli and Klebsiella pneumoniae) even though cobalt(II) complexes are well known for their activity against gram positive bacteria.